Exchange Rate Movements and its Local Effects: Turkey Case - Duran, Hasan Engin (International Journal of Economics and Financial Issues, 2016)
Aim of the current study is to investigate the impact of exchange rate movements on regional growth and inequalities across 26 NUTS-2 level regions in Turkey over a period 2004-2011. In terms of methodology, Spatial-Panel methods such as Fixed and Random Effect estimators alligned with Spatial Autoregressive and Error models were adopted. As an outcome, it has been shown that depreciation of Turkish lira creates an increasing effect on aggregate growth while its impact on regions are quite mixed. The industrialized Western regions are worsely affected. In these regions, depreciations create an increase in the cost items of companies, discouraging the production and output growth. Controversially, relatively less developed regions in Eastern parts are positively affected from depreciations, probably due to their improved export performances, following a depreciation, driven by a decrease in exported-good prices and increased competitiveness in foreign markets. This leads consequently to an improvement of convergence process. Keywords: Exchange Rate, Regional growth, Spatial-Panel Models JEL Clasifications: F31, F32, R11, R12